STRATEGIC BUSINESS TRANSFORMATION AND CORPORATE SUSTAINABILITY: EXAMINING THE ROLE OF DYNAMIC AND DIGITAL CAPABILITIES - Situmorang, Patar; Purba, John Tampil; Hariandja, Evo Sampetua (Jurnal Manajemen, 2025)
In today's dynamic and competitive business environment, organizations must continuously adapt to external and internal changes to achieve corporate sustainability. This study examines the influence of Business  Transformation (BT), Service Innovation Capability (SIC), and Service Delivery (SD) on Corporate Sustainability (CS), with Dynamic Capability (DC) as a mediating variable and Digital Transformation (DT) as a moderate factor. Employing Resource-Based View (RBV) and Market-Based View (MBV) theories, this study aims to explore how firms leverage internal capabilities and external market factors to drive long-term sustainability. A quantitative research design was applied, utilizing "This study employed Partial Least Squares-Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses, utilizing data collected from 400 managers." and executives in the energy sector, with a focus on PT PLN (Persero). The findings confirm that BT, SIC, and SD positively influence CS, both directly and indirectly through DC. Furthermore, DT significantly moderates the relationships between BT, SIC, and SD with DC, indicating that digital adoption enhances firms' ability to adapt and reconfigure resources. The mediating role of DC was also supported, reinforcing its importance in linking strategic initiatives to sustainability outcomes. This study contributes to strategic management literature by integrating RBV and MBV perspectives while providing empirical evidence on DT as a catalyst for corporate sustainability. Practically, the results highlight the importance of firms investing in digital capabilities.", service innovation, and dynamic adaptation strategies to remain competitive. Future research should explore longitudinal effects and industry variations in digital transformation and sustainability practices.